Cytokine adsorber use during DCD heart perfusion counteracts coronary microvascular dysfunction - Saemann, Lars; Hoorn, Fabio; Georgevici, Adrian-Iustin; Pohl, Sabine; Korkmaz-İçöz, Sevil; Veres, Gábor; Guo, Yuxing; Karck, Matthias; Simm, Andreas; Wenzel, Folker; Szabó, Gábor (Antioxidants, 2022)
Microvascular dysfunction (MVD) in cardiac allografts is associated with an impaired endothelial function in the coronary microvasculature. Ischemia/reperfusion injury (IRI) deteriorates endothelial function. Hearts donated after circulatory death (DCD) are exposed to warm ischemia before initiating ex vivo blood perfusion (BP). The impact of cytokine adsorption during BP to prevent MVD in DCD hearts is unknown. In a porcine DCD model, we assessed the microvascular function of hearts after BP with (DCD-BPCytoS, n = 5) or without (DCD-BP, n = 5) cytokine adsorption (CytoSorb®). Microvascular autoregulation was assessed by increasing the coronary perfusion pressure, while myocardial microcirculation was measured by Laser-Doppler-Perfusion (LDP). We analyzed the immunoreactivity of arteriolar oxidative stress markers nitrotyrosine and 4-hydroxy-2-nonenal (HNE), endothelial injury indicating cell adhesion molecules CD54, CD106 and CD31, and eNOS. We profiled the concentration of 13 cytokines in the perfusate. The expression of 84 genes was determined and analyzed using machine learning and decision trees. Non-DCD hearts served as a control for the gene expression analysis. Compared to DCD-BP, relative LDP was improved in the DCD-BPCytoS group (1.51 ± 0.17 vs. 1.08 ± 0.17). Several pro- and anti-inflammatory cytokines were reduced in the DCD-BPCytoS group. The expression of eNOS significantly increased, and the expression of nitrotyrosine, HNE, CD54, CD106, and CD31, markers of endothelial injury, majorly decreased in the DCD-BPCytoS group. Three genes allowed exact differentiation between groups; regulation of HIF1A enabled differentiation between perfusion (DCD-BP, DCD-BPCytoS) and non-perfusion groups. CAV1 allowed differentiation between BP and BPCytoS. The use of a cytokine adsorption device during BP counteracts preload-dependent MVD and preserves the microvascular endothelium by preventing oxidative stress and IRI of coronary arterioles of DCD hearts.
Gesehen am 30.01.2023